2017
DOI: 10.1007/978-3-662-55751-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Fast Delivery by Mobile Agents

Abstract: We consider the problem of delivering m messages between specified source-target pairs in a weighted undirected graph, by k mobile agents initially located at distinct nodes of the graph. Each agent consumes energy proportional to the distance it travels in the graph and we are interested in optimizing the total energy consumption for the team of agents. Unlike previous related work, we consider heterogeneous agents with different rates of energy consumption (weights w i ). To solve the delivery problem, agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…They provided 2-resource-augmented algorithm for general graphs in this setting and showed that it is the best possible solution that can be computed in polynomial time. Other variants of collaborative delivery that have been considered are when agents have distinct rate of energy consumption [21] or when the agents have distinct speeds [22]. In these cases the optimization criteria is to minimize the total energy consumption and/or the total time taken for delivery.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They provided 2-resource-augmented algorithm for general graphs in this setting and showed that it is the best possible solution that can be computed in polynomial time. Other variants of collaborative delivery that have been considered are when agents have distinct rate of energy consumption [21] or when the agents have distinct speeds [22]. In these cases the optimization criteria is to minimize the total energy consumption and/or the total time taken for delivery.…”
Section: Related Workmentioning
confidence: 99%
“…Another related work [23] studied the collective delivery problem for selfish agents that try to optimize their personal gain. See also [24] for a survey of recent results on collaborative delivery by agents with energy limitations.…”
Section: Related Workmentioning
confidence: 99%
“…In [12] it is shown that deciding whether the agents can deliver the data is (weakly) NP-complete. Additional research under various conditions and topological assumptions can be found in [4] which studies the game-theoretic task of selecting mobile agents to deliver multiple items on a network and optimizing or approximating the total energy consumption over all selected agents, in [2,5,7] which study data delivery and combine energy and time efficiency, and in [18,19] which are concerned with collaborative exploration in various topologies.…”
Section: Related Workmentioning
confidence: 99%
“…Additional research under various conditions and topological assumptions can be found in [2] which studies the game-theoretic task of selecting mobile agents to deliver multiple items on a network and optimizing or approximating the total energy consumption over all selected agents, in [3] which studies data delivery and combines energy and time efficiency, and in [11,12] which is concerned with collaborative exploration in various topologies.…”
Section: Related Workmentioning
confidence: 99%